Edukasi Gemar Menabung Sejak Dini Melalui Kegiatan Mewarnai Celengan di SD Negeri 1 Gelam - Adynda Dara Meylia,; Novisah,; Nurhasbiyah Maya Iswanti,; Siti Maimunah, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The habit of saving from an early age is a crucial strategy in fostering responsible financial character in children. The consumptive behavior among elementary school students indicates that most children do not yet understand the importance of setting aside pocket money for long-term needs. The "Saving Awareness and Piggy Bank Coloring" program at SD Negeri Gelam 1 was designed to introduce basic financial management concepts in a creative and enjoyable way. This activity aims to build students' financial awareness and motivation to save regularly.This study employed a qualitative descriptive approach involving 53 fifth-grade students at SD Negeri Gelam 1. The activity was conducted on July 28, 2025, as part of a Community Service Program (KKN) by university students. The steps included delivering a brief session on the benefits of saving, distributing plain piggy banks, coloring activities, presenting the finished products, and a reflection and Q&A session. Data were collected through observation, photo documentation, and informal interviews with students and teachers, and were analyzed descriptively to capture changes in student attitudes. The results revealed high enthusiasm among students, demonstrated by their active participation in every stage of the activity. Approximately 85% of students showed a positive shift in attitudes toward saving, reflected in their commitment to regularly fill their piggy banks at home. Teachers also observed ongoing discussions about savings among students after the activity. These findings suggest that art-based learning methods can be an effective strategy for instilling financial literacy values from an early age.